Method for recovering and repairing lithium iron phosphate positive electrode material through transient high-temperature impact and application
Repairing lithium iron phosphate electrode sheets through transient high temperature impact technology solves the problems of long processing time and high energy consumption in traditional recycling methods, achieves rapid and efficient material repair and electrochemical performance improvement, and promotes the sustainability of battery cycles .
Patent Information
- Application Number
- CN202411675480.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-21
AI Technical Summary
The traditional lithium iron phosphate (LFP) battery recycling method has long processing time, high energy consumption and complex pretreatment steps, which impairs the sustainability of the LFP cycle.
Transient high temperature shock (HTS) technology is used to repair the waste lithium iron phosphate electrode sheet. The binder on the surface of the lithium iron phosphate electrode sheet is carbonized and deactivated through a short-term high-temperature treatment, and the missing lithium is supplemented with the lithium hydroxide aqueous solution. Then vacuum drying and high temperature shock were carried out again to obtain the repaired lithium iron phosphate positive electrode material.
The rapid and efficient repair of lithium iron phosphate positive electrode materials is achieved, significantly improving electrochemical performance, reducing energy consumption and processing time, and promoting a more sustainable battery cycle method.
Smart Images

Figure CN119490170A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries, and specifically relates to a method and application of transient high-temperature impact recovery and repair of lithium iron phosphate positive electrode materials. Background Art
[0002] Lithium iron phosphate (LiFePO4, LFP) batteries have attracted much attention in the field of lithium-ion batteries (LIBs) due to their high sustainability, thermal stability, long service life and low cost. These advantages have enabled LFP batteries to occupy more than one-third of the entire LIBs market and currently dominate the fields of power tools, electric buses and grid energy storage, but have also led to an increasing number of waste batteries. Improper handling of these waste batteries will cause a large amount of resource waste and have a significant impact on the environment. Unfortunately, traditional battery recycling based on hydrometallurgy not only produces a large amount of pollutants and wastewater emissions, but is also economically unprofitable due to the limited value of LFP, thus undermining the sustainability of resource utilization. Direct recycling of LFP materials allows it to have a simpler route, significantly reduce emissions, and greatly improve the profitability of LFP recycling by retaining and repairing the structure of the active material for battery reuse. In aged or degraded LFP, material failure usually has three reasons: (1) reduction of active lithium. During long-term cycling, active lithium will form SEI film at the negative electrode and react with electrolyte to generate various inorganic lithium or organic lithium compounds. These substances are not electrochemically active. (2) Related to Li / Fe mixing, the reduction of active lithium leads to the formation of Li vacancies (LiV), Fe occupying Li sites (FeLi), and Li / Fe anti-sites in the crystal unit. These three defects almost always coexist. Since the transport of lithium ions in LFP is one-dimensional, these anti-site Li / Fe defects (FeLi, Li / Fe anti-sites) inevitably hinder the diffusion of lithium ions. (3) Shedding of carbon coating. With the long-term cycling of lithium-ion batteries, the internal temperature of the battery rises, and the uniformity of LFP is poor. Some places heat up faster, resulting in the early shedding of the carbon layer in these places. These are the main reasons for the capacity decline in LFP.
[0003] Conventional direct recycling requires high-temperature annealing for several hours, which not only leads to long processing time and high energy consumption compared to LFP resynthesis, but also requires multiple pretreatment steps to remove other impurities (such as binders and Al current collectors in LFP electrodes) to avoid harmful side reactions during the later sintering process. Obviously, these pretreatments increase the complexity of the regeneration process and damage the sustainability of the LFP cycle.
[0004] Therefore, there is an urgent need to provide a method for quickly and efficiently recovering and repairing lithium iron phosphate positive electrode materials. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for recycling and repairing lithium iron phosphate positive electrode materials; the second purpose of the present invention is to provide a repaired lithium iron phosphate positive electrode material; the third purpose of the present invention is to provide an application of the lithium iron phosphate positive electrode material obtained by recycling and repairing the method in the preparation of lithium-ion batteries; the fourth purpose of the present invention is to provide a lithium-ion battery comprising the repaired lithium iron phosphate positive electrode material.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a method for recovering and repairing lithium iron phosphate positive electrode materials, comprising the following steps:
[0008] Step 1: placing the lithium iron phosphate pole piece taken out from the waste battery on carbon paper, and subjecting it to a short high-temperature shock in an argon atmosphere to carbonize and inactivate the binder on the surface of the lithium iron phosphate pole piece and separate the aluminum foil to obtain the peeled lithium iron phosphate powder;
[0009] Step 2: The stripped lithium iron phosphate powder is evenly dispersed by ball milling, and then added into a lithium hydroxide aqueous solution and stirred for reaction to supplement the missing lithium;
[0010] Step 3, centrifuging the solution after the reaction in step 2, and vacuum drying the solid product after centrifugation;
[0011] Step 4: placing the vacuum-dried solid product in a crucible and subjecting it to transient high-temperature shock in an argon atmosphere to obtain a repaired lithium iron phosphate positive electrode material.
[0012] Considering the defects of traditional recycling processes, in the present invention, the inventors use transient high temperature shock (HTS) technology. Unlike traditional high temperature manufacturing processes, HTS can reach a peak temperature of 3000K in seconds or milliseconds through huge energy drive in an instant, with ultra-fast heating and cooling rates, and most of the products prepared by this method have extremely small Gibbs free energy only in a local range, which is not the most stable state, and is a thermodynamically unstable product. This kinetic-dominated feature makes it show great advantages in the exploration and controllable preparation of new materials (such as high entropy components, thermodynamically metastable phases and surface defects that cannot be obtained by conventional methods). This is a method to induce fast, diffusion-free "jumping" movement of anti-localized lithium-iron pairs in the lattice structure. This process promotes the rapid and coherent reordering of lithium-iron atoms at the interatomic level. Impressively, this reconfiguration unfolds in just a few milliseconds, which is too short for any harmful side reactions (impurity generation, phase destruction, etc.) to occur, demonstrating the efficiency and precision of high-temperature superconductors in manipulating atomic structures without compromising the integrity of the material. At the same time, the HTS process can selectively carbonize the polyvinylidene fluoride (PVDF) binder instantly to form a fluorine-doped carbon coating on the LFP particles; when the composite CEI is combined with the surface lithium supplement, the electronic conductivity and lithium conductivity can be significantly improved, so that the regenerated LFP has higher electrochemical performance. This fast and efficient HTS process also proves that the technical solution of the present invention has significant technical, economic and environmental benefits, thereby promoting a more sustainable battery cycle method.
[0013] In the above method, preferably, the battery is selected from a lithium iron phosphate power battery, a lithium iron phosphate battery for an energy storage base station, or a lithium iron phosphate battery with a cycle SOC ≥ 70%; but not limited thereto.
[0014] In the above method, preferably, the lithium iron phosphate sheet is taken out after the battery is discharged to below 2V.
[0015] In the above method, preferably, in step 1, the conditions of the short high temperature shock are temperature 400-500° C., voltage 60-75 V, current 25-30 A, and shock time 1-3 s.
[0016] In the above method, preferably, the binder is selected from polyvinylidene fluoride; but not limited thereto.
[0017] In the above method, preferably, in step 2, the concentration of the lithium hydroxide aqueous solution is 0.05-0.5 mol / L.
[0018] In the above method, preferably, in step 2, the stirring reaction temperature is 40 to 60° C., and the reaction time is 20 to 40 min.
[0019] In the above method, preferably, in step three, the centrifugal speed is 5000-8000 r / min.
[0020] In the above method, preferably, the vacuum drying temperature is 60-80° C., and the drying time is 2-5 hours.
[0021] In the above method, preferably, in step 4, the conditions of the transient high temperature shock are temperature 650-750°C, voltage 100-120V, current 70-90A, and shock time 20-30s.
[0022] On the other hand, the present invention also provides a repaired lithium iron phosphate positive electrode material, which is prepared by recycling and repairing using the above-mentioned method.
[0023] On the other hand, the present invention also provides the lithium iron phosphate positive electrode material obtained by recycling and repairing the above method or the use of the above repaired lithium iron phosphate positive electrode material in the preparation of lithium ion batteries.
[0024] In another aspect, the present invention further provides a lithium-ion battery, which comprises the lithium iron phosphate positive electrode material prepared by recycling and repairing the above method or the above repaired lithium iron phosphate positive electrode material.
[0025] Beneficial effects of the present invention:
[0026] The present invention utilizes transient high-temperature impact technology to quickly and efficiently repair lithium iron phosphate pole piece waste without damaging the integrity of the material, and at the same time, instantly carbonizes the PVDF binder on the surface of the lithium iron phosphate pole piece waste to form a F-doped carbon coating on the lithium iron phosphate particles; when the composite CEI is combined with the surface lithium supplement, the electronic conductivity and lithium conductivity can be significantly improved, so that the regenerated lithium iron phosphate positive electrode material has higher electrochemical performance.
[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 The figure is a comparison chart of the cycle performance of the lithium ion batteries prepared in Examples 1 to 3 of the present invention and Comparative Example 1 at different rates. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0031] Embodiment 1:
[0032] This embodiment provides a method for recycling and repairing lithium iron phosphate positive electrode materials, and the specific steps are as follows:
[0033] (1) After the soft-pack battery with a SOC (state of charge) of 70% was discharged to 2V, the lithium iron phosphate electrode was taken out and placed on carbon paper, and then subjected to high temperature (400°C) shock for 1s in an argon atmosphere at 60V / 25A to inactivate the binder polyvinylidene fluoride (PVDF) on the surface of the lithium iron phosphate electrode and separate the aluminum foil to obtain the peeled lithium iron phosphate powder;
[0034] (2) The exfoliated lithium iron phosphate powder was placed in an agate mortar and ball-milled to disperse it evenly. 25 g of the ball-milled lithium iron phosphate was added to 100 mL of a 0.08 mol / L lithium hydroxide aqueous solution for stirring reaction. The mixture was stirred at 45° C. for 30 min to replenish the lost lithium.
[0035] (3) centrifuging the solution after the reaction in step (2) at 8000 r / min, and drying the solid product after centrifugation in a vacuum oven at 70° C. for 3 h;
[0036] (4) The solid product after vacuum drying in step (3) is placed in a crucible and subjected to high temperature (700° C.) impact for 20 seconds in an argon atmosphere at 110 V / 72 A to obtain a repaired lithium iron phosphate positive electrode material.
[0037] This embodiment also provides the assembly of a lithium-ion battery using the repaired lithium iron phosphate positive electrode material obtained by the recycling and repair method, and the specific steps are as follows:
[0038] The lithium iron phosphate positive electrode material obtained above, the conductive agent acetylene black and the adhesive PVDF (80:15:5wt%) and the NMP solvent were mixed and slurried, and then evenly coated on the Al foil. After vacuum drying for 12 hours, it was punched into 12mm uniform discs as spare positive electrodes; CR2016 batteries were assembled in an Ar atmosphere glove box with water and oxygen values <1ppm, the electrolyte was 1mol / L LiPF6 / EC-DMC (1:1, volume ratio), the negative electrode was a metal lithium sheet, and the diaphragm was a commercial diaphragm, and the battery was assembled.
[0039] Embodiment 2:
[0040] This embodiment provides a method for recycling and repairing lithium iron phosphate positive electrode materials, and the specific steps are as follows:
[0041] (1) After the soft-pack battery with a SOC (state of charge) of 70% was discharged to 2V, the lithium iron phosphate electrode was taken out and placed on carbon paper, and then subjected to high temperature (400°C) shock for 1s in an argon atmosphere at 60V / 25A to inactivate the binder polyvinylidene fluoride (PVDF) on the surface of the lithium iron phosphate electrode and separate the aluminum foil to obtain the peeled lithium iron phosphate powder;
[0042] (2) The exfoliated lithium iron phosphate powder was placed in an agate mortar and ball-milled to disperse it evenly. 25 g of the ball-milled lithium iron phosphate was added to 100 mL of a 0.08 mol / L lithium hydroxide aqueous solution for stirring reaction. The mixture was stirred at 45° C. for 30 min to replenish the lost lithium.
[0043] (3) centrifuging the solution after the reaction in step (2) at 8000 r / min, and drying the solid product after centrifugation in a vacuum oven at 70° C. for 3 h;
[0044] (4) The solid product after vacuum drying in step (3) is placed in a crucible and subjected to high temperature (650° C.) impact for 20 seconds in an argon atmosphere at 100 V / 72 A to obtain a repaired lithium iron phosphate positive electrode material.
[0045] This embodiment also provides the assembly of a lithium-ion battery using the repaired lithium iron phosphate positive electrode material obtained by the recycling and repair method, and the specific steps are as follows:
[0046] The lithium iron phosphate positive electrode material obtained above, the conductive agent acetylene black and the adhesive PVDF (80:15:5wt%) and the NMP solvent were mixed and slurried, and then evenly coated on the Al foil. After vacuum drying for 12 hours, it was punched into 12mm uniform discs as spare positive electrodes; CR2016 batteries were assembled in an Ar atmosphere glove box with water and oxygen values <1ppm, the electrolyte was 1mol / L LiPF6 / EC-DMC (1:1, volume ratio), the negative electrode was a metal lithium sheet, and the diaphragm was a commercial diaphragm, and the battery was assembled.
[0047] Embodiment 3:
[0048] This embodiment provides a method for recycling and repairing lithium iron phosphate positive electrode materials, and the specific steps are as follows:
[0049] (1) After the soft-pack battery with a SOC (state of charge) of 70% was discharged to 2V, the lithium iron phosphate electrode was taken out and placed on carbon paper, and then subjected to high temperature (400°C) shock for 1s in an argon atmosphere at 60V / 25A to inactivate the binder polyvinylidene fluoride (PVDF) on the surface of the lithium iron phosphate electrode and separate the aluminum foil to obtain the peeled lithium iron phosphate powder;
[0050] (2) The exfoliated lithium iron phosphate powder was placed in an agate mortar and ball-milled to disperse it evenly. 25 g of the ball-milled lithium iron phosphate was added to 100 mL of a 0.08 mol / L lithium hydroxide aqueous solution for stirring reaction. The mixture was stirred at 45° C. for 30 min to replenish the lost lithium.
[0051] (3) centrifuging the solution after the reaction in step (2) at 8000 r / min, and drying the solid product after centrifugation in a vacuum oven at 70° C. for 3 h;
[0052] (4) The solid product after vacuum drying in step (3) is placed in a crucible and subjected to high temperature (750° C.) impact for 20 seconds in an argon atmosphere at 120V / 72A to obtain a repaired lithium iron phosphate positive electrode material.
[0053] This embodiment also provides the assembly of a lithium-ion battery using the repaired lithium iron phosphate positive electrode material obtained by the recycling and repair method, and the specific steps are as follows:
[0054] The lithium iron phosphate positive electrode material obtained above, the conductive agent acetylene black and the adhesive PVDF (80:15:5wt%) and the NMP solvent were mixed and slurried, and then evenly coated on the Al foil. After vacuum drying for 12 hours, it was punched into 12mm uniform discs as spare positive electrodes; CR2016 batteries were assembled in an Ar atmosphere glove box with water and oxygen values <1ppm, the electrolyte was 1mol / L LiPF6 / EC-DMC (1:1, volume ratio), the negative electrode was a metal lithium sheet, and the diaphragm was a commercial diaphragm, and the battery was assembled.
[0055] Comparative Example 1:
[0056] For comparison, in this comparative example, after the soft pack battery with SOC (state of charge) of 70% is discharged to 2V, the lithium iron phosphate pole piece is taken out for battery assembly. The specific steps are as follows:
[0057] The removed lithium iron phosphate pole piece, conductive agent acetylene black and adhesive PVDF (80:15:5wt%) and NMP solvent were mixed and slurried, and then evenly coated on Al foil. After vacuum drying for 12 hours, it was punched into 12mm uniform discs as spare positive electrodes; CR2016 batteries were assembled in an Ar atmosphere glove box with water and oxygen values <1ppm. The electrolyte was 1mol / L LiPF6 / EC-DMC (1:1, volume ratio), the negative electrode was a metal lithium sheet, and the diaphragm was a commercial diaphragm, and the battery was assembled.
[0058] The battery cycle performance test of the batteries prepared in the above Examples 1 to 3 and Comparative Example 1 was carried out. The experimental results are as follows: Figure 1 shown.
[0059] Depend on Figure 1 The experimental results show that the cycle performance results at different rates show that at a rate of 0.1C, the capacity of the LFP material of the embodiment after repair by the method of the present invention is restored to about 156 mAh / g, while the capacity of the LFP material of the comparative example is only 147 mAh / g at 0.1C. Under different rate cycles, the embodiments have good performance, and also have good performance at a high rate (2C).
[0060] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for recovering and repairing lithium iron phosphate positive electrode material, characterized in that: The steps include: Step 1: placing the lithium iron phosphate pole piece taken out from the waste battery on carbon paper, and subjecting it to a short high-temperature shock in an argon atmosphere to carbonize and inactivate the binder on the surface of the lithium iron phosphate pole piece and separate the aluminum foil to obtain the peeled lithium iron phosphate powder; Step 2: The stripped lithium iron phosphate powder is evenly dispersed by ball milling, and then added into a lithium hydroxide aqueous solution and stirred for reaction to supplement the missing lithium; Step 3, centrifuging the solution after the reaction in step 2, and vacuum drying the solid product after centrifugation; Step 4: placing the vacuum-dried solid product in a crucible and subjecting it to transient high-temperature shock in an argon atmosphere to obtain a repaired lithium iron phosphate positive electrode material.
2. The method according to claim 1, characterized in that: The battery is selected from a lithium iron phosphate power battery, a lithium iron phosphate battery for an energy storage base station, or a lithium iron phosphate battery with a cycle SOC ≥ 70%; Preferably, the lithium iron phosphate sheet is removed after the battery is discharged to below 2V.
3. The method according to claim 1, characterized in that: In step 1, the conditions of the short high temperature shock are temperature 400-500°C, voltage 60-75V, current 25-30A, and shock time 1-3s; Preferably, the binder is selected from polyvinylidene fluoride.
4. The method according to claim 1, characterized in that: In step 2, the concentration of the lithium hydroxide aqueous solution is 0.05-0.5 mol / L.
5. The method according to claim 1, characterized in that: In step 2, the stirring reaction temperature is 40-60° C., and the reaction time is 20-40 min.
6. The method according to claim 1, characterized in that: In step 3, the centrifugal speed is 5000-8000 r / min; Preferably, the vacuum drying temperature is 60-80° C., and the drying time is 2-5 hours.
7. The method according to claim 1, characterized in that: In step 4, the conditions of the transient high temperature shock are temperature 650-750° C., voltage 100-120 V, current 70-90 A, and shock time 20-30 s.
8. A repaired lithium iron phosphate positive electrode material, which is prepared by recycling and repairing using the method described in any one of claims 1 to 7.
9. Use of the lithium iron phosphate cathode material obtained by recycling and repairing the method according to any one of claims 1 to 7 or the repaired lithium iron phosphate cathode material according to claim 8 in preparing lithium-ion batteries.
10. A lithium-ion battery comprising a lithium iron phosphate positive electrode material prepared by recycling and repairing the method according to any one of claims 1 to 7 or a repaired lithium iron phosphate positive electrode material according to claim 8.